Morphometric Evaluation of Collateral Ligaments of the First Metacarpophalangeal Joint - Gnanasekaran, Dhivyalakshmi; Raveendranath, Veeramani; Karupusamy, Aravindhan (Journal of Hand and Microsurgery, 2020)
Introduction The collateral ligaments of the first metacarpophalangeal (MCP) joint provide stability to the thumb. Injury to these collateral ligaments occurs more commonly in sports accidents leading to joint instability, weakness in pinch and grip strength. Normal morphometric measurements of collateral ligaments are essential for primary repair or reconstruction of the injured ligament. Hence, the objective of the study is to give the detailed morphometric profile of the proper collateral ligaments of the MCP joint of the thumb.Materials and Methods A total of 55 adult cadaveric hands were included in the study taken from 18 male (36 hands) and 10 female (19 hands) cadavers. Out of 55 hands, 28 belonged to the left side, while 27 were of the left side. The MCP joints were dissected to expose the collateral ligament complex. The length and width of the proper ligaments were measured.Results Both the proper collateral ligament attachments and the direction of the fibers were defined. Overall length and the width of both the proper collateral ligaments showed no statistically significant difference of mean between the left and the right sides. However, the length of both the proper collateral ligaments is significantly less in females compared with the males.Conclusion The morphometric details of the proper collateral ligaments obtained from this study would be useful for hand surgeons during surgical correction of the injured collateral ligaments either by primary repair or reconstruction with a tendon graft.
Keywords: collateral ligaments; thumb; morphometry; reconstruction